Kode Etik Akuntan Publik Dalam Perspektif Pedoman Fundamental Islam - Lusiana, Eva (Owner : Riset dan Jurnal Akuntansi, 2024)
The preparation of “the professional code of ethics for Public Accountants (AP) has been designed in detail. However, in practice violations of the AP professional code of ethics still occur frequently. This research aims to provide reviews for the drafting team of the Code of Ethics for the Professional Public Accountant to pay more attention and reconsider the principles of faith and adherence to Islamic values ??based on the Al-Quran and As-Sunnah. This study uses library research to collect research data. The researcher collects information on Islamic values ??related to the important role of ethics in life and analyzes it so that it can be internalized into the next draft of the Code of Ethics for the Professional Public Accountant. The implementation of the principles of faith and adherence to Islamic values ??will work well if Islamic character education is taught to each AP and prospective AP” through academic and non-academic activities.